Analisis Budaya Masyarakat Suku Aceh di Kecamatan Medan Tembung , Kota Medan - Sakira Putri Manurung; Dwidya Nuari; Sanas Tasia Sihaloho; Kiki Renhardi Napitupulu; Rohani Rohani; Elsa Kardiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Since the time of the archipelago, Acehnese culture has maintained a rich and intricate cultural legacy. Due to its advantageous position and status as a commerce route, Acehnese culture was influenced by the cultures of many of the traders that passed through. The purpose of this study is to learn about Acehnese culture from a social and physical standpoint. The information gained from this study's findings will undergo qualitative analysis. With the help of interview rules, this data collecting method is conducted by asking informants questions directly and verbally (face-to-face). In order to generate qualitative data, researchers perform qualitative analysis by giving a detailed and understandable explanation of the problem information. Based on the outcomes of interviews conducted by researchers, the Acehnese tribal community has similarities between physical and social behavior that are still applied in everyday life which are usually presented at traditional events, religious celebrations and cultural celebrations and the Acehnese tribal community is also famous for its traditional traditions and strong religion and highly upheld norms that are still applied in everyday life. These norms include Islamic religious norms, legal norms originating from the Islamic Religion and the 1945 Constitution, politeness norms in dressing in accordance with Islamic teachings, moral norms that closely related to Islamic teachings, and social norms such as courtesy, mutual respect, mutual cooperation and mutual assistance. In this research, it can be concluded that the Acehnese people who live around Medan Tembung sub-district, Medan city, actually still adhere to several norms which are an integral part of their identity and daily life. And also has customs. Social practices and traditions that have been maintained for generations by the Acehnese people reflect the richness of their culture and spirituality. And the Acehnese language not only functions as a means of communication, but also as a symbol of regional identity and pride for the Acehnese people